The Effect of Live Streaming Sales and Store Atmosphere Digital on Generation Z Impulsive Buying Decisions in TikTok Shop (A Case Study in Kelurahan Abianbase) - I Gusti Ngurah Bayu Segara; I Gusti Ngurah Sanjaya; Wayan Gede Suka Parwita (ProBisnis : Jurnal Manajemen, 2026)
This study aims to determine the partial and simultaneous effects of live streaming sales and store atmosphere digital on impulsive buying decisions among Generation Z at TikTok Shop. Conducted in Kelurahan Abianbase, this quantitative research utilized a purposive sampling method, gathering primary data from 130 respondents through structured questionnaires. The data were analyzed using multiple linear regression. The results demonstrated that live streaming sales exerted a positive and significant effect on impulsive buying. Similarly, store atmosphere digital had a positive and significant impact. Simultaneously, both variables significantly enhanced impulsive buying decisions. Strategic recommendations include standardizing real-time information delivery during live sessions and establishing a uniform visual design for digital stores.